Effectiveness of Facilitation Services for Repatriation of Indonesian Migrant Workers at Technical Implementation Unit of Labor and Transmigration Office in East Java Province - Dwingga Aprilliana Futri Gunawan; Binti Azizatun Nafi'ah (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This study examines the effectiveness of the Indonesian Migrant Workers Deportation Facilitation Service at the UPT-P2TK of the East Java Provincial Manpower and Transmigration Office using descriptive qualitative research methods. This study analyzes the effectiveness of the Indonesian Migrant Worker Deportation Repatriation Facilitation Service which includes the quality, efficiency, and responsiveness of services provided to deported Indonesian Migrant Workers. This study concluded that the Effectiveness of the Indonesian Migrant Worker (PMI) Deportation Repatriation Facilitation Service uses the theory The focus of this research focuses on using the effectiveness of Fandy Tjiptono's public services (2017) in (Pane et al., 2020), of which there are 4 (Four) Indicators, namely: Service Timeliness, Service Accuracy, Courtesy and Friendliness in providing services, and ease of getting services. which can show whether the facilitation services provided by UPT-P2TK regarding the facilitation of PMI deportation repatriation are running effectively. Keywords: Deportation Repatriation, Effectiveness, Facilitation Services, Indonesian Migrant Workers.